KEPUTUSAN PEMBELIAN PRODUK HAIR CARE LOVE BEAUTY AND PLANET - Rachma Alya Hapsari Kusumayanti (2022)
One of the most urgent environmental problems today is environmental pollution by plastic waste. This problem is one of the concerns of consumers before making a decision to buy a product. This study was conducted to analyze and prove the effect of green promotions, green products and e-WOM on purchasing decisions for Love Beauty And Planet hair care products. This study used a sample of 75 respondents and used a non-probability sampling technique with purposive sampling. Data was obtained using a questionnaire with the criteria of respondents aged 17 years and over, domiciled in DKI Jakarta, and had purchased Love Beauty And Planet hair care products at least once. This research uses descriptive data analysis technique, validity test, and reliability test. Hypothesis testing in this study used the analysis of the outer model, inner model, and t-statistical test using the SmartPLS 3.0 test tool. This study shows that green promotion and green products have a positive and significant effect on purchasing decisions for Love Beauty And Planet hair care products. However, e-WOM does not have a significant effect on purchasing decisions for Love Beauty And Planet hair care products.